Livestock auction evaluated as an investment project by the Upala Chamber. - Morales Abarca, Ana Lucía (2019)
The Chamber of Cattlemen of Upala is an organization formed by 140 producers, with two years of foundation. Created in order to show solidarity with producers after Hurricane Otto, which occurred in 2016 affecting the north area of ​​Costa Rica. The project is an economic and technical analysis for the possible establishment of a livestock auction in the area of ​​Upala, Costa Rica for the year 2019. The differentiating element would be a competitive commission margin before the nearby auctions and a direct administration that it benefits the camera and the cattle ranchers. The project was carried out by reviewing secondary information, expert consults, scheduled visits and financial indicators, this in order to generate a contextual framework of the scope of the activity from a financial angle and with respect to the main technical requirements for maximum operation. The main results of the investigation were: an initial investment of ₡ 13 717 644,65; where infrastructure disbursements and other items that increase this item are not incurred, an internal positive rate of return of 32,92%, a value current net of ₡ 2 615 472,31 derived from the activity through a capital cost rate of 15,01% and a return period of 3.45 years. As a recommendation, the implementation of this project analyzed from the technical and economic approaches shows that there is feasibility to carry out the project, which due to its magnitude is an option that enhances the strengthening of the chamber and provides them with preparation for future larger projects.